The Effect of Different Ages on the Body Dimensions of Intensively Raised Balinese Cattle in Samarinda City - Suhardi, Suhardi; Abdullah, Asep Junaedi; Wibowo, Ari (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2024)
This study aimed to find out the effect of different ages on the body dimensions of Bali cattle which are reared intensively to select calves. This study was designed using a completely randomized design (CRD) which consisted of 3 treatments, namely different ages of cattle with the same repetition. Based on the results of the analysis of variance, it was shown that the age of the cows had a significant effect on the body dimensions of Bali cattle which were reared intensively. Based on the least significant difference test (LSD) showed that the P3 treatment was higher than the P1 and U2 treatments. While the treatment of P1 and P2 is relatively the same. This is because P1 and P2 are the phases of bone growth while at P3 the bone growth is maximized leading to fat accumulation. Based on the results of the study it can be concluded that the selection of breeding stock can be carried out by taking into account the body dimensions of Bali cattle where aged 2.5-3 years have body dimensions such as body length, chest circumference, hip height, shoulder height, chest width and crotch width which are larger. better than age 1.5-2.5 and 2–2.5 years.